Idiopathic Intracranial Hypertension Without Papilledema (IIHWOP) in Chronic Refractory Headache - Favoni, Valentina; Pierangeli, Giulia; Toni, Francesco; Cirillo, Luigi; La Morgia, Chiara; Abu-Rumeileh, Samir; Messia, Monica; Agati, Raffaele; Cortelli, Pietro; Cevoli, Sabina (Frontiers in Neurology, 2018)
Background To determine the prevalence of Idiopathic intracranial hypertension without papilledema (IIHWOP) testing revised diagnostic criteria by Friedman in refractory chronic headache (CH) patients. Methods This is a prospective observational study. Each patient underwent ophthalmologic evaluation and Optical Coherence Tomography; brain magnetic resonance venography (MRV) and a lumbar puncture (LP) with opening pressure (OP) measurement. CSF withdrawal was performed in patients with CSF OP>200 mmH20. IIHWOP was defined according Friedman’s diagnostic criteria. Effect of CSF withdrawal was evaluated clinically in a 6 month follow-up and with a MRV study at 1 month. Results Forty-five consecutive patients were enrolled. Five were excluded due to protocol violations. Analyses were conducted in 40 patients (32 F, 8 M; mean age 49.4±10.8). None had papilledema. Nine patients (22.5%) had OP greater than 200mmH2O, two of them above 250 mmH2O. Two (5%) had neuroimaging findings suggestive of elevated intracranial pressure. One of them (2.5%) met the newly proposed diagnostic criteria by Friedman for IIHWOP. After CSF withdrawal seven (77.8%) of the nine patients improved. No changes in neuroimaging findings were found. Conclusions We found a low prevalence (2.5%) of IIHWOP in refractory CH patients according to current diagnostic criteria. In agreement with Friedman’s criteria, our results confirm that a diagnosis of IIHWOP should be based on CSF OP and the combination of neuroradiological findings. However, where to set the CSF OP upper limit in IIHWOP needs further field testing. Although IIHWOP is a rare clinical condition, it should be considered and treated in refractory CH patients.